Treatment of refractory juvenile idiopathic arthritis via pulse therapy using methylprednisolone and cyclophosphamide - Castro, Tania Caroline Monteiro de; Terreri, Maria Teresa; Len, Claudio; Hilário, Maria Odete Esteves (São Paulo Medical Journal, 2003)
CONTEXT: Patients with refractory juvenile idiopathic arthritis can benefit from aggressive therapy. CASE REPORT: We followed the clinical course of 4 patients (2 male, 2 female) aged 9.1-17.8 years (mean of 14.5 years) with polyarticular onset of juvenile rheumatoid arthritis and one 16-year old boy with juvenile spondyloarthropathy associated with inflammatory bowel disease. All the juvenile rheumatoid arthritis patients fulfilled the diagnostic criteria established by the American College of Rheumatology. All patients had unremitting arthritis despite maximum therapy. All patients began receiving treatment using intravenous cyclophosphamide at 500-750 mg/m2 and intravenous methylprednisolone at 30 mg/ kg, for 3 days monthly (1 g maximum). The patients received between 3 and 11 monthly treatments, and/or 3-5 treatments every two months for 12 months, according to the severity of the disease and/or response to the therapy. All but one patient were evaluated retrospectively at the start (time 0) and 6 months (time 1), and 12 months (time 2) after the beginning of the treatment. A rapid and clinically significant suppression of systemic and articular manifestations was seen in all patients. Our results showed the favorable effect of this treatment on the clinical and some laboratory manifestations of juvenile idiopathic arthritis.